Raoul Wallenberg w Sowietach od 1945 roku [znaczek podziemny] . Raoul Wallenberg in Soviet Russia since 1945. Unofficial stamp - Poczta Polska. (Poczta Polska, 1987)
Black print on white paper, without perforation Stamp, with "Poczta Polska" imprint, represents Raoul Wallenberg behind bars. Price: 40 zł per stamp.